Association of High‐Sensitivity Cardiac Troponin T and N‐Terminal Pro–Brain‐Type Natriuretic Peptide With Left Ventricular Structure: J‐HOP Study. Issue 5 (8th May 2014) - Hoshide, Satoshi; Nagai, Michiaki; Yano, Yuichiro; Ishikawa, Joji; Eguchi, Kazuo; Kario, Kazuomi; the Japan Morning Surge‐Home Blood Pressure Study Investigators Group
<x xml:space="preserve">Abstract</x> Although both high‐sensitivity cardiac troponin T (Hs‐cTnT) and N‐terminal pro–brain‐type natriuretic peptide (NT‐proBNP) levels are higher among patients with cardiac structural abnormalities than among those with apparently normal hearts, there is considerable overlap between the groups. The authors evaluated 1336 patients who had ≥1 cardiovascular risk factors, underwent echocardiography, and had Hs‐cTnT and NT‐proBNP measured and excluded patients with left ventricular (LV) dysfunction. The patients in the highest Hs‐cTnT category in quintiles had an increased likelihood of abnormal relative wall thickness compared with those in the lowest category (odds ratio, 1.66; 95% confidence interval, 1.17–2.36; P<.01). However, no such association was found in the category of NT‐proBNP. The patients in the highest NT‐proBNP category had an increased likelihood of abnormal LV diastolic dimension/body surface area compared with those in the lowest category (odds ratio, 2.11; 95% confidence interval, 1.17–3.79; P<.05). However, no such association was found in the category of Hs‐cTnT. The data suggest that the measurement of Hs‐cTnT and NT‐proBNP might provide information on cardiac structural abnormalities.